Anti-colorectal cancer effects of seaweed-derived bioactive compounds - Fu, Yunhua; Xie, Dong; Zhu, Yinghao; Zhang, Xinyue; Yue, Hao; Zhu, Kai; Pi, Zifeng; Dai, Yulin (Frontiers in Medicine, 2022)
Seaweeds are classified as Chlorophyta, Rhodophyta, and Phaeophyta. They constitute a number of the most significant repositories of new therapeutic compounds for human use. Seaweed has been proven to possess diverse bioactive properties, which include anticancer property. The present review focuses on colorectal cancer, which is a primary cause of cancer-related mortality in humans. In addition, it discusses various compounds derived from a series of seaweeds that have been shown to eradicate or slow the progression of cancer. Therapeutic compounds extracted from seaweed have shown activity against colorectal cancer. Furthermore, the mechanisms through which these compounds can induce apoptosis in vitro and in vivo were reviewed. This review emphasizes the potential utility of seaweeds as anticancer agents through the consideration of the capability of compounds present in seaweeds to fight against colorectal cancer.